Pengaruh Permen Jahe Terhadap Frekuensi Mual Muntah Pada Ibu Hamil Trimester I - Bahrah Bahrah; Mirna Wigunarti (Malahayati Nursing Journal, 2022)
ABSTRACT Emesis gravidarum is one of the most common complaints and affects millions of pregnant women worldwide each year and is still experienced by 85% of all pregnancies. Several pharmacological therapies are considered to treat nausea, which has recently been recommended to treat nausea and vomiting in pregnant women, namely the administration of vitamin B6, but it is less effective because many pregnant women are afraid to take medication, so non-pharmacological therapies are recommended, one of which is ginger. The purpose of this study was to evaluate the effect of ginger candy on the frequency of nausea and vomiting in first trimester pregnant women in the Amban Public Health Center, Manokwari Regency. This study analyzed the frequency of nausea and vomiting after being given ginger candy. This type of research is a quasi-experimental research with a control group pre-test and post-test design. The sample in this study were pregnant women who experienced nausea and vomiting in the first trimester in the Amban Health Center working area as many as 20 respondents with a sampling technique using purposive sampling. This study conducted an analysis of the frequency of nausea and vomiting in pregnant women before and after being given ginger candy intervention for 7 days according to the SOP for giving ginger candy with a dose of giving ginger candy intervention as much as 4 packages in 1 day, where each package of ginger candy contains about 250 mg of ginger candy. and sugar was given and Vitamin B6 200 mg/day for 7 days. The research instrument used was the PUQE questionnaire. The data taken are primary data and data analysis using parametric and non-parametric tests. The results showed that there were differences in the frequency of nausea and vomiting scores before and after treatment in the intervention group with p value value (0.05) and there was no difference in the frequency of nausea and vomiting scores before and after treatment in the control group with p value value. (0.05). The conclusion is that ginger candy affects the frequency of nausea and vomiting in pregnant women in the first trimester after being given an intervention.  Keywords : Pregnant Women, Frequency of Nausea Vomiting, Ginger Candy ABSTRAK Emesis gravidarum merupakan salah satu keluhan yang paling umum dan mempengaruhi jutaan perempuan hamil diseluruh dunia setiap tahunnya dan masih dialami oleh 85% dari semua kehamilan. Beberapa terapi farmakologi dipertimbangkan untuk mengatasi mual yang baru-baru ini direkomendasikan untuk mengatasi mual muntah pada ibu hamil yaitu pemberian vitamin B6 namun kurang efektif karena banyak ibu hamil yang takut untuk minum obat sehingga direkomendasikan terapi non farmakologis yaitu salah satunya pemberian jahe. Tujuan dari penelitian ini adalah untuk mengevaluasi pengaruh permen jahe terhadap frekuensi mual muntah Pada Ibu Hamil Trimester I Di Wilayah Kerja Puskesmas Amban Kabupaten Manokwari. Penelitian ini melakukan analisis frekuensi mual muntah setelah diberikan permen jahe. Jenis penelitian ini adalah penelitian quasy experiment dengan rancangan penelitian control group pre test and post test design. Sampel dalam penelitian ini adalah ibu hamil yang mengalami mual muntah Trimester I di Wilayah Kerja Puskesmas Amban sebanyak 20 responden dengan teknik pengambilan sampel menggunakan purposive sampling. Penelitian ini melakukan analisis frekuensi mual muntah pada ibu hamil sebelum dan setelah diberikan intervensi permen jahe selama 7 hari sesuai SOP pemberian permen jahe dengan dosis pemberian pemberian intervensi permen jahe sebanyak 4 kemasan dalam 1 hari, dimana setiap kemasan permen jahe mengandung sekitar 250 mg permen jahe dan gula diberikan dan Vitamin B6 200 mg/hari selama 7 hari.  Instrumen penelitian yang digunakan adalah kuisioner PUQE. Data yang diambil merupakan data primer dan analisa data menggunakan uji parametrik dan non parametrik test. Hasil penelitian menunjukan bahwa terdapat perbedaan skor frekuensi mual muntah sebelum dan sesudah perlakuan pada kelompok intervensi dengan nilai p value nilai α (0,05)  dan tidak terdapat perbedaan skor frekuensi mual muntah sebelum dan sesudah perlakuan pada kelompok kontrol dengan nilai p value nilai α (0,05). Kesimpulan yaitu permen jahe berpengaruh terhadap frekuensi mual muntah pada ibu hamil trimester I setelah diberikan intervensi. Kata kunci: Ibu Hamil, Frekuensi Mual Muntah, Permen Jahe